2006
DOI: 10.1128/aac.50.3.917-921.2006
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of the Activities of Currently Available Antifungal Agents against 3,378 Spanish Clinical Isolates of Yeasts and Filamentous Fungi

Abstract: We have compared the activities of posaconazole and other currently available antifungal agents against a collection of 3,378 clinical isolates of yeasts and filamentous fungi. A total of 1,997 clinical isolates of Candida spp., 359 of other yeast species, 697 strains of Aspergillus spp., and 325 nondermatophyte non-Aspergillus spp. were included. The average geometric means of the MICs of agents that were tested against Candida spp. were 0.23 g/ml for amphotericin B, 0.29 g/ml for flucytosine, 0.97 g/ml for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
175
4
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(199 citation statements)
references
References 28 publications
14
175
4
6
Order By: Relevance
“…Here attention may also be drawn to the reports of breakthrough Trichosporon infection in leukaemic patients receiving caspofungin therapy (Matsue et al, 2006;Chitasombat et al, 2012). Trichosporon spp., although belonging to the basidiomycetous lineage, are similar in their arthroconidial morphological characteristics as well as in susceptibility profile to echinocandins (Cuenca-Estrella et al, 2006;Miceli et al, 2011). As echinocandins are now being used as first-line drugs for the treatment of Candida infections, it is important that yeast isolates are accurately identified and antifungal susceptibility determined before an echinocandin is prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Here attention may also be drawn to the reports of breakthrough Trichosporon infection in leukaemic patients receiving caspofungin therapy (Matsue et al, 2006;Chitasombat et al, 2012). Trichosporon spp., although belonging to the basidiomycetous lineage, are similar in their arthroconidial morphological characteristics as well as in susceptibility profile to echinocandins (Cuenca-Estrella et al, 2006;Miceli et al, 2011). As echinocandins are now being used as first-line drugs for the treatment of Candida infections, it is important that yeast isolates are accurately identified and antifungal susceptibility determined before an echinocandin is prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…All isolates described so far have been fluconazolesensitive (Lockhart et al, 2008). This is not necessarily the case with other uncommonly identified non-albicans Candida species (Cuenca-Estrella et al, 2006). Given the range of fluconazole susceptibility, early rationalization of antifungal use may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…These were tested by various methods including broth microdilution (Antifungal Susceptibility Testing Subcommittee of the European Committee on Antibiotic Susceptibility Testing for testing fermentative yeasts) and Etest (AB Biodisk) (Cuenca-Estrella et al, 2006;Tay et al, 2009). All isolates described so far have been fluconazolesensitive (Lockhart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the new triazoles, voriconazole and posaconazole, as well as a combined treatment should be considered as a possible option to modify outcome. 41,[44][45] Even though the antifungal drugs registered for empiric therapy (AmB formulations and caspofungin) are not intrinsically active against Scedosporium spp, the very low incidence of scedosporiosis also in AML patients does not justify the use of other antifungal drugs active against these highly pathogenic fungi in the empiric setting.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Our literature review showed that therapeutic options for S. prolificans infection are more limited because of its resistance profile: in vitro susceptibility studies have invariably demonstrated an almost total resistance to AmB and to other available antifungal agents. 41 However, voriconazole has shown some promising in vitro activity, alone or in combination with terbinafine. 40,[42][43] The routine use of these new antifungal drugs seems to suggest an improved outcome in the future.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%